Experimental demonstration of weak chirality enhancement by hybrid perovskite nanocrystals using photonic spin Hall effect - Lai Zheng; Lin Shuai; Shi Youzhi; Li Maoxin; Liu Guangyou; Tian Bingbing; Chen Yu; Zhou Xinxing (Nanophotonics)
Chiral perovskites have attracted considerable attention as excellent spin-emitting materials for applications in spintronics, quantum optics, and biological. Especially in drug development of biological, weak chirality molecules are frequently selected to reduce the side effects of toxics, and there is a common defect for accurately detecting the weak chirality with common methods at room temperature. In this study, formamidine lead bromide perovskite nanocrystals (FAPbBr3 NCs) were coated with chiral ligands, whose chirality was too weak to be observed in the visible region at room temperature. Thus, by characterizing the transverse shift of photonic spin Hall effect (SHE), the accurate discrimination of weak chirality in the visible region was achieved successfully. By measuring the shift value and light spot splitting of photonic SHE at the same concentration, NEA-coated FAPbBr3 NCs can effectively enhance the chirality of naphthalene ethylamine (NEA) ligands when under the mutually reinforcement of chiral molecular and inorganic parts. In addition, we furtherly clearly distinguished the tiny chiral distinction of NEA-coated FAPbBr3 NCs with different particle sizes, which revealed that the chirality decreases with the increase of particle size. These findings could provide effective solutions for the detection and application of weak chirality in hybrid perovskite nanocrystals in universal environment.